2020
DOI: 10.5964/jspp.v8i2.1362
|View full text |Cite
|
Sign up to set email alerts
|

Mistrust and misinformation: A two-component, socio-epistemic model of belief in conspiracy theories

Abstract: Although conspiracy theories are endorsed by about half the population and occasionally turn out to be true, they are more typically false beliefs that, by definition, have a paranoid theme. Consequently, psychological research to date has focused on determining whether there are traits that account for belief in conspiracy theories (BCT) within a deficit model. Alternatively, a two-component, socio-epistemic model of BCT is proposed that seeks to account for the ubiquity of conspiracy theories, their variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 170 publications
8
83
2
1
Order By: Relevance
“…First, the current findings show that distrust does not only increase conspiracy beliefs but also interacts with factors related to information processing, like education level and scientific literacy. Contrary to the implicit assumption (Pierre, 2020), better reasoning capacity did not suppress the effect of social factors in the current research; it instead exacerbated the relevance of social inclusiveness. This is possibly due to lack of education and scientific literacy causing a ceiling effect on conspiracy beliefs, rendering the social context relatively less influential, while people with high levels of these qualities interpret the social context and rationally become more suspicious of potential conspiracies if social indicators suggest exclusion from prosperous alliances.…”
Section: Overview Of the Findings And Contributions To The Literaturecontrasting
confidence: 99%
See 1 more Smart Citation
“…First, the current findings show that distrust does not only increase conspiracy beliefs but also interacts with factors related to information processing, like education level and scientific literacy. Contrary to the implicit assumption (Pierre, 2020), better reasoning capacity did not suppress the effect of social factors in the current research; it instead exacerbated the relevance of social inclusiveness. This is possibly due to lack of education and scientific literacy causing a ceiling effect on conspiracy beliefs, rendering the social context relatively less influential, while people with high levels of these qualities interpret the social context and rationally become more suspicious of potential conspiracies if social indicators suggest exclusion from prosperous alliances.…”
Section: Overview Of the Findings And Contributions To The Literaturecontrasting
confidence: 99%
“…In a similar vein, Pierre (2020) has recently argued that epistemic mistrust, which is a consequence of the perceived unreliability of the authoritative sources, drives people to look for alternative, unofficial explanations (Pierre, 2020; also see van Mulukom et al, 2021).…”
Section: Overview Of the Findings And Contributions To The Literaturementioning
confidence: 99%
“…These include traditional fact-checking and debunking approaches (Ecker et al, 2020;Paynter et al, 2019), and also reminding people to think carefully about the accuracy of online information and consider the credibility of the source before sharing information on social media (Pennycook et al, 2020). It should also be noted that building trust in government and health authorities will be a protective factor, as mistrust is one of the drivers of conspiracy beliefs (Pierre, 2020).…”
Section: Pandemic Communications: Foundations and Recommendationsmentioning
confidence: 99%
“…It has been theorized that distrust in other individuals, groups, and organizations is crucial in driving people toward conspiracy theories (van Mulukom et al, 2021). It has further been suggested that mistrust triggers biased information processing (e.g., lower analytical thinking and scientific literacy) which eventually results in conspiracy beliefs (Pierre, 2020). Recently, lack of trust in media (Bruder & Kunert, 2021;Lockyer et al, 2021;Su et al, 2021), government and public health institutions (Bruder & Kunert, 2021;De Coninck et al, 2021;Kim & Kim, 2021;Pummerer et al, 2021), and science (Constantinou et al, 2020;Eberl et al, 2021;Erceg et al, 2020) have also been shown to play a key role in fostering conspiracy beliefs about the origins of COVID-19.…”
Section: Conspiracy Beliefs and Generosity Across 52 Countries During The Covid-19 Pandemicmentioning
confidence: 99%